Effect of local toroidal flow on double‐tearing modes in cylindrical geometry. Issue 9 (9th June 2020) - Zhang, Ruibo; Lu, Xingqiang; Guo, Wei; Yin, Chenyan; Gong, Xueyu
Abstract: The effect of local toroidal flow (LTF) on double‐tearing modes (DTMs) is investigated in cylindrical geometry using the reduced magnetohydrodynamics (RMHD) model. The results indicate that the LTF between the two rational surfaces is the dominant suppression effect on DTMs. The suppression effect is enhanced with the flow width increasing, and the DTMs become more stable with the increase of the shear of the LTF between the two rational surfaces. So, in the reversed shear magnetic field configuration, the local flow is driven between the two rational surfaces, which can effectively suppress the development of DTMs and maintain the high‐performance state.